2017
DOI: 10.1093/epolic/eix001
|View full text |Cite
|
Sign up to set email alerts
|

You’re banned! The effect of sanctions on German cross-border financial flows

Abstract: Reproduction permitted only if source is stated.ISBN 978-3-95729-249-0 (Printversion) Non-technical summaryResearch Question This paper examines the effect of financial sanctions on cross-border capital flows. While sanctions can be expected to hinder international transactions, thereby putting political and economic pressure on a target country, we study the patterns of adjustment in bilateral relationships after the imposition of a sanction along various dimensions. For instance, in addition to aggregate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 14 publications
7
54
0
Order By: Relevance
“…Another related strand is the literature on the trade effects of sanctions, which have been shown to be important in, among others, the cases of South Africa (Evenett, 2002), Germany when it comes to capital flows (Besedeš, Goldbach, & Nitsch, 2017, Iran (Haidar, 2017) and Russia (Crozet & Hinz, 2016;Oja, 2015). 9 Oja (2015) focused on Russia's counter-sanctions using product-level data from the Baltic states; his results support the rather lukewarm overall impact of sanctions originating from the Ukraine crisis.…”
Section: Gullstrandmentioning
confidence: 99%
See 1 more Smart Citation
“…Another related strand is the literature on the trade effects of sanctions, which have been shown to be important in, among others, the cases of South Africa (Evenett, 2002), Germany when it comes to capital flows (Besedeš, Goldbach, & Nitsch, 2017, Iran (Haidar, 2017) and Russia (Crozet & Hinz, 2016;Oja, 2015). 9 Oja (2015) focused on Russia's counter-sanctions using product-level data from the Baltic states; his results support the rather lukewarm overall impact of sanctions originating from the Ukraine crisis.…”
Section: Gullstrandmentioning
confidence: 99%
“…Hence, trade deflection reflects the efficiency of sanctions, since the cost of sanctions on the target economy falls when it could find other markets. Besedeš, Goldbach, and Nitsch (2017), Crozet and Hinz (2016), Evenett (2002) and Haidar (2017) all investigated the importance of both trade destruction and deflection using firm-level data, but in very different settings and with different results. Evenett (2002) and Haidar (2017) found evidence of a strong trade deflection, which mitigated the impact of sanctions directed towards South Africa and Iran, respectively.…”
Section: The Impact Of Sanctionsmentioning
confidence: 99%
“…For instance, Haidar () showed that two‐thirds of Iranian exports were deflected to non‐sanctioning countries after trade sanctions by Western countries. For similar reasons, international financial sanctions can also distort cross‐border capital flows as shown by Besedes, Goldbach, and Nitsch (). Applying a differences‐in‐differences approach, they found that European financial sanctions significantly reduced direct financial flows with the sanctioned country, and they also led to evasions as capital flows increased among European countries and the major trading partners of sanctioned countries which were assumed to be more likely to serve as intermediaries.…”
Section: Literature Reviewmentioning
confidence: 82%
“…6 Wang et al 2019. 7 Hatipoglu and Peksen 2018;Besedeš et al 2017;Mirkina 2018. 8 Hufbauer et al 1990 Although there exists a voluminous literature exploring the impact of economic sanctions on drivers of economic growth, it is quite surprising that there is a lack of empirical evidence on the direct impact of economic sanctions on economic growth.…”
Section: Introductionmentioning
confidence: 99%